USM VC PROPOSES DEVELOPING ISLAMIC RESEARCH METHODOLOGIES – STRENGTHENING TIES WITH INDONESIAN UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
JEMBER, INDONESIA, September 2015 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman has proposed for the swift development of Islamic research methodologies to replace the commonlyused methodologies which do not take into account religious priorities, more so in the context of the Muslim communities.